Evaluasi Library Automation System Professional (LIANSPRO) di Perpustakaan - Prabowo, Digdo Dwi Amtoko; Wardoyo, Dewie Tri Wijayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to describe the Management of the Library Automation System Professional (LIANSPRO) at the Al Hikmah Elementary School Surabaya Library using the Human Organizing Technology (HOT) Fit Model system evaluation method. This study uses a qualitative method with a case study research design. Collecting data using interview, observation, and documentation studies. Data analysis uses data condensation, data presentation, and drawing conclusions. The validity of the data in this study was tested for credibility, transferability test, dependability test, and confirmability test. The results showed (1) good and supportive technology, supportive organizational structure and environment, and convenience and usefulness for users of the lianspro system that provided an effective and efficient impact with excellent service at the Al Hikmah Elementary School Surabaya library. The technological, organizational, and human components show the results of the system evaluation using the HOT Fit Model method which explains that the implementation of the lianspro system in the Al Hikmah Elementary School Surabaya library is running well and provides benefits for the development of a literacy culture in schools; and (2) In the application of the lianspro system at the Al Hikmah Elementary School Surabaya library, there are several obstacles both in process and management. In conclusion, the results of this study indicate that the use of a professional library automation system provides excellent service to visitors to the Al Hikmah Elementary School Surabaya library. Keywords: Management, Lianspro System, and Libraries